2016
DOI: 10.1007/s00402-016-2457-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the interaction between contact force and decision making on lower extremity biomechanics during a side-cutting maneuver

Abstract: The GRF and muscle activities were smaller in the first peak than those in the second peak; however, first peak showed a closer association with biomechanical risk factors of the ACL injury. There were some interactions between contact force and decision making and unanticipation made the first peak more risky to the ACL injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
0
1
1
Order By: Relevance
“…These results are consistent with the present research, but the rate of changes of these parameters was different, and this difference may be due to different-testing conditions and subjects. However, Kim et al showed that unpredictable cutting maneuver leads to a significant increase in knee flexion [29]. This research result is not consistent with the available results, and this difference can be due to the gender difference of the subjects.…”
Section: Discussioncontrasting
confidence: 57%
“…These results are consistent with the present research, but the rate of changes of these parameters was different, and this difference may be due to different-testing conditions and subjects. However, Kim et al showed that unpredictable cutting maneuver leads to a significant increase in knee flexion [29]. This research result is not consistent with the available results, and this difference can be due to the gender difference of the subjects.…”
Section: Discussioncontrasting
confidence: 57%
“…Ⅰ 緒言 バスケットボール,サッカーやアメリカンフットボールなどの球技スポーツ場面におい ては,あらゆる方向への動きが混在し,急激な減速や加速がみられる.高い速度で方向転換 を行う能力は,脚筋力や体幹の向き,接地時間などの要因によって影響されることが報告さ れている (Marshall et al, 2014) .さらに,素早い方向転換走パフォーマンスの決定要因と して,加速局面と減速局面における力積や床反力,接地時間が挙げられている (Houck et al, 2006;Kim et al, 2016;Lee et al, 2017;Spiteri et al, 2015…”
unclassified